A novel meta-heuristic optimization algorithm: Thermal exchange optimization. (August 2017) - Kaveh, A.; Dadras, A.
Highlights: A new optimization algorithm based on Newton's law of cooling is developed. This new algorithm is called Thermal Exchange Optimization (TEO) algorithm. Newton's law of cooling states that the rate of heat loss of a body is proportional to the difference in temperatures between the body and its surroundings. Each agent is considered as a cooling object and by associating another agent as environment, a heat transferring happens between these agents. The new temperature of the object is considered as its next position in the search space. Abstract: This paper introduces a new optimization algorithm based on Newton's law of cooling, which will be called Thermal Exchange Optimization algorithm. Newton's law of cooling states that the rate of heat loss of a body is proportional to the difference in temperatures between the body and its surroundings. Here, each agent is considered as a cooling object and by associating another agent as environment, a heat transferring and thermal exchange happens between them. The new temperature of the object is considered as its next position in search space. The performance of the algorithm is examined by some mathematical functions and four mechanical benchmark problems.